Ultrasound‐Guided Approaches to Improve Orthotopic Mouse Xenograft Models for Hepatocellular Carcinoma. Issue 2 (30th May 2019) - Bou About, Ghina; Thiebault, Emilie; Wattenhofer‐Donzé, Marie; Jacobs, Hugues; Guimond, Alain; Sorg, Tania; Robinet, Eric; Baumert, Thomas F.; Monassier, Laurent; Herault, Yann
Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer death worldwide. While curative approaches for early stage HCC exist, effective treatment options for advanced HCC are lacking. Furthermore, there are no efficient chemopreventive strategies to limit HCC development once cirrhosis is established. One challenge for drug development is unsatisfactory animal models. In this article, we describe an orthotopic xenograft mouse model of human liver cancer cell lines through image‐guided injection into the liver. This technique provides a less invasive yet highly efficient approach to engraft human HCC into mouse liver. Similarly, image‐guided injections are used to deliver chemotherapeutics locally, enabling reduction in potential systemic adverse effects, while reducing the required dose for a therapeutic effect. In summary, this image‐guided strategy provides a novel and convenient approach to improve current HCC mouse models. © 2019 The Authors. This is an open access article under the terms of the Creative Commons Attribution‐NonCommercial‐NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non‐commercial and no modifications or adaptations are made.